Interface between the production plan and the master production schedule in assembly environments - Moya-Navarro, Marcos (2012)
In a production environment there is a direct relationship between the market and the manufacturing process of goods.When production is immersed in an assembly environment, the process of production planning and scheduling becomes complex, and the enterprises have the risk of losing competitive advantages in terms of not meeting delivery dates and production high costs. Linear programming has become an appropriate tool for production planning and scheduling in complex manufacturing environments. The aim of this paper is to show the interface between both the production process planning and the scheduling process in assembly environments by means of linear programming.The manufacturing process selected is capable of producing three products with a product structure arranged on three levels with a maximum of eight components each. Data provided by the aggregate production planning was grouped into ten production orders with information of product type, quantity to be produced and their respective delivery date. Final results were orders placement and components required in order to minimizing the cost of issuing orders and inventory costs.